Use of Nanotechnologies in the Field of Construction Material Science (Texas Journal of Multidisciplinary Studies, 2023)
This article analyzed the theoretical and practical issues of the use of nanotechnology in solving the main problems of the field of construction materials and environmental protection. It is said that nanotechnology has a huge economic potential for use in all areas, and it helps to increase efficiency and environmental cleanliness at all stages